Body mass, temperature, and pathogen intensity differentially affect critical thermal maxima and their population‐level variation in a solitary bee - Laura J. Jones; Douglas A. Miller; Rudolf J. Schilder; Margarita M. López‐Uribe (Ecology and Evolution, 2024)
Abstract Climate change presents a major threat to species distribution and persistence. Understanding what abiotic or biotic factors influence the thermal tolerances of natural populations is critical to assessing their vulnerability under rapidly changing thermal regimes. This study evaluates how body mass, local climate, and pathogen intensity influence heat tolerance and its population‐level variation (SD) among individuals of the solitary bee Xenoglossa pruinosa. We assess the sex‐specific relationships between these factors and heat tolerance given the differences in size between sexes and the ground‐nesting behavior of the females. We collected X. pruinosa individuals from 14 sites across Pennsylvania, USA, that varied in mean temperature, precipitation, and soil texture. We measured the critical thermal maxima (CTmax) of X. pruinosa individuals as our proxy for heat tolerance and used quantitative PCR to determine relative intensities of three parasite groups—trypanosomes, Spiroplasma apis (mollicute bacteria), and Vairimorpha apis (microsporidian). While there was no difference in CTmax between the sexes, we found that CTmax increased significantly with body mass and that this relationship was stronger for males than for females. Air temperature, precipitation, and soil texture did not predict mean CTmax for either sex. However, population‐level variation in CTmax was strongly and negatively correlated with air temperature, which suggests that temperature is acting as an environmental filter. Of the parasites screened, only trypanosome intensity correlated with heat tolerance. Specifically, trypanosome intensity negatively correlated with the CTmax of female X. pruinosa but not males. Our results highlight the importance of considering size, sex, and infection status when evaluating thermal tolerance traits. Importantly, this study reveals the need to evaluate trends in the variation of heat tolerance within and between populations and consider implications of reduced variation in heat tolerance for the persistence of ectotherms in future climate conditions.